Dental Treatment Need Among First-Visit Patients Of Dental Outpatient Clinic At IIUM Kuantan For The Year 2016 - Ismail, Azlini; Abllah, Zurainie; Muhammad Radhi, Nur Aishah; Musa, Syazalina; Abdul Halim, Mohd Firdaus Akbar (IIUM Medical Journal Malaysia, 2017)
Introduction: This cross-sectional study aimed to determine association of age and gender with dental treatment need among first-visit patients at Dental Outpatient Clinic, IIUM Kuantan in 2016. Materials and Methods: Ethical approval (IREC 762) was obtained from IIUM Human Ethics Committee. List of first-visit patients who attended clinic from 1st January to 31st December 2016 was retrieved to assess patient's age and gender. Dental treatment need was determined according to the normative need which was professionally defined by dental-officer-in-charge. All first-visit patients were included, except those attended Orthodontic department or with old Malaysian identification card or foreign passport. Included patients were classified into six age groups (≤14, 15-19, 20-34, 35-44, 45-64 and ≥ 65). Pearson's chi square test was used for statistical analysis using SPSS Version 20 software. Results: From a total number of 2,713 patients (age range of 2 to 87), 1,210 (44.6%) were males and 1,503 (55.4%) were females. Age (p<0.001) and gender (p<0.001) were significantly associated with dental treatment need. Paediatric patients (≤14) majorly received paedodontic care (97.5%). Young-age patients (15-19, 20-34 and 35-44) mostly required conservative care (39.5%, 31.2% & 30.6%, respectively) while elder-age patients (45-64 and ≥ 65) have major need for prosthodontics (30.0% & 40.2%, respectively). Females outnumbered males in all age groups, except for the age group of ≥ 65 whereby the situation was the opposite. Females also outnumbered males in all types of treatment need, except for periodontics which was predominated by males. Conclusion(s): Age and gender have significant associations with treatment need for dental care.